Experiences and perceptions of people with celiac disease, food allergies and food intolerance when dining out - Figueroa-Gómez, Ximena; Oliveras-López, María Jesus; Rodríguez Silva, Juan Manuel; Poyanco, Marcelo; López, Herminia; Araya, Magdalena (Frontiers in Nutrition, 2024)
Eating out is a common practice in modern society. Celiac disease (CeD) and food allergy (FA) are among the most common conditions responsible for adverse reactions to food. Despite their different origins, both require treatment with restrictive diets (avoidance of gluten and/or specific allergens) and this results posing similar challenges when eating out. Our objective was to learn about the experiences/perceptions of consumers with CeD and FA when dining out, as well as the challenges they face in food service environments. An ad hoc questionnaire was used to record consumer perceptions, food service characteristics and resulting adverse reactions. 377 individuals living in Santiago, Chile, provided complete information and were analyzed (160 CeD, 105 FA). 301 participants (79.8%) declared eating out, 33.6% reported experiencing an adverse reaction at least once while eating out. 94.4% of the 377 participants believed that the serving staff had little or no knowledge about his/her condition. Consumers reporting symptoms as severe adverse reactions were more common among celiac than allergic patients (p<0.001). The study showed no significant differences based on consumer-related characteristics (NS). The consequences of eating out did not vary based on individual's data, including diagnosis, age, frequency of eating out, adverse reactions experienced, or intensity. These findings suggest that the most important determinants of risk associated with eating out are characteristics of the food service, like availability of information, staff training, and establishment's facilities like equipment available, exclusive utensils for customers with special dietary needs and kitchen and bathrooms organization.